The role of hypoestrogenism on Mmp-8 and Mmp-13 gene expression in maxilla and mandible's growth sites. Issue 1 (2nd January 2022) - Calixto, Robson Diego; Ayumi Omory, Marjorie; Ramazzotto, Lucas Alexandre; Madalena, Isabela Ribeiro; Hueb de Menezes Oliveira, Maria Angélica; Donadelli Nabarro, Humberto Madson; Moro, Alexandre; Nelson-Filho, Paulo; Scariot, Rafaela; Küchler, Erika Calvano
ABSTRACT: Purpose: The aim of this study was to assess whether hypoestrogenism influenced the gene expression (mRNA) of Mmp-8 and Mmp-13 at maxilla and mandible growth sites. Materials and Methods: Twelve female Wistar rats in the prepubertal period (21 days-old) were randomly divided into 2 groups: OVX (which underwent ovariectomy surgery – hypoestrogenism animals) and SHAM (which underwent fictitious ovariectomy surgery – control animals). At 45 days-old (during puberty) euthanasia was performed. The growth centres (palatal suture, mandibular condyle, coronoid process, mandibular angle, symphysis, and mandibular parasymphysis) were dissected. For gene expression analysis, the RNA was extracted and cDNA synthesis was performed on total RNA. The real-time PCR technique was used to analyse the gene expression of Mmp-8 and Mmp-13 . Statistical analysis was performed with a level of significance of 5%. Results: Statistical significance was observed only between the mandibular condyle and the mRNA expression of Mmp-8 ( p = 0.03 ), where there was an increase in the expression of this gene in the OVX group. Conclusion: Hypoestrogenism upregulated Mmp-8 gene expression in the mandibular condyle during puberty period of the rats in the study. This may be one of the mechanisms in which oestrogen is involved in mandible growth and development during prepubertal period.